2023
DOI: 10.3390/life13071437
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium subsp. paratuberculosis Antigens Elicit a Strong IgG4 Response in Patients with Multiple Sclerosis and Exacerbate Experimental Autoimmune Encephalomyelitis

Abstract: Neuroinflammation can be triggered by microbial products disrupting immune regulation. In this study, we investigated the levels of IgG1, IgG2, IgG3, and IgG4 subclasses against the heat shock protein (HSP)70533–545 peptide and lipopentapeptide (MAP_Lp5) derived from Mycobacterium avium subsp. paratuberculosis (MAP) in the blood samples of Japanese and Italian individuals with relapsing remitting multiple sclerosis (MS). Additionally, we examined the impact of this peptide on MOG-induced experimental autoimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…To perform the peptide-based indirect ELISA, we employed the Imject maleimideactivated bovine serum albumin (BSA) spin kit from Thermo Fisher Scientific, Waltham, MA, USA, as previously published [19]. This kit was selected to ensure that antigenic epitopes remain accessible for antibody binding, preventing any masking effect.…”
Section: Peptide-based Indirect Enzyme-linked Immunosorbent Assays (E...mentioning
confidence: 99%
See 2 more Smart Citations
“…To perform the peptide-based indirect ELISA, we employed the Imject maleimideactivated bovine serum albumin (BSA) spin kit from Thermo Fisher Scientific, Waltham, MA, USA, as previously published [19]. This kit was selected to ensure that antigenic epitopes remain accessible for antibody binding, preventing any masking effect.…”
Section: Peptide-based Indirect Enzyme-linked Immunosorbent Assays (E...mentioning
confidence: 99%
“…It has been hypothesized that the EBV, a globally widespread γ-herpes virus capable of establishing latent infection with periodic reactivation, contributes to the pathogenesis of MS, either directly by infecting B cells [17] or indirectly by interacting with other genetic and environmental factors, such as the activation of neuropathogenic human endogenous retroviruses [18]. In a recent study conducted on Japanese and Sardinian subjects, we identified antibodies showing cross-reactivity between EBNA1 386-405 and a peptide belonging to Mycobacterium avium paratuberculosis heat shock protein 70 [19]. M. paratuberculosis is a bacterium endemic in the Sardinian Island, which has been proposed as a potential risk factor for MS in susceptible individuals, and its encephalitogenic potential in experimental autoimmune encephalomyelitis (EAE) has been demonstrated [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation